PATHOMORPHOLOGICAL ASPECTS OF GESTATIONAL PYELONEPHRITIS DEVELOPED ON THE BACKGROUND OF PREGNANCY - Tojiboev , Temurbek; Mamataliyeva , Madina (International Journal of Scientific Pediatrics, 2024)
Pyelonephritis is one of the most common kidney diseases in pregnant women. Opportunistic microorganisms prevail in the etiology of pregnancy pyelonephritis (mainly enterobacteria and enterococci (23%)). With the recurrence of chronic pyelonephritis, pregnancy is often complicated by preeclampsia, and the risk of developing infectious and inflammatory diseases in newborns increases. The urgency of the problem of pyelonephritis is the presence of infectious and septic complications in the fetus and expectant mother and its negative impact on the expansion of the upper urinary tract that occurs during pregnancy. The development of pregnancy increases the chronic course of pyelonephritis, leads to frequent attacks of renal colic, causes kidney failure.